Carvernous hemangioma of spleen - Trostchansky, Julio; Colet, Andrés; Rondán, Mariela (Cirugía del Uruguay, 2005)
Splenic héemangiomas are the most benign among sp/enic tumors. They are, however, a rarity (0.03%).